Peranan Guru Pendidikan Agama Hindu dan Budi Pekerti dalam Membentuk Karakter Profil Pelajar Pancasila pada Siswa Kelas X di SMK Negeri 1 Denpasar - Mahendra, I Gede; Sueca, I Nyoman; Indrayani, A.A. Diah (UHN IGB Sugriwa Denpasar, 2025)
The Character of the Pancasila Student Profile represents the embodiment of lifelong learners who are competent, possess strong character, and behave in accordance with the values ​​of Pancasila. This research focuses on an in-depth analysis of three main aspects, namely: (1) the implementation of Hindu Religious Education and Character Education in shaping the character of the Pancasila Student Profile; (2) the learning models employed by teachers in developing the Pancasila Student Profile; and (3) the impact of the role of Hindu Religious Education and Character Education teachers in shaping the Pancasila Student Profile. Specifically, this study aims to identify the implementation of Hindu Religious and Character Education learning, the applied learning models, and to describe the impact of the role of Hindu Religious and Character Education teachers in developing the Pancasila Student Profile at SMK Negeri 1 Denpasar. This study employs a theoretical framework encompassing cognitive, constructivist, and behaviorist perspectives. The research subjects include Hindu Religious and Character Education teachers and all tenth-grade students. Data collection techniques used in this study consist of observation, interviews, and documentation. The collected data were analyzed using a qualitative descriptive analysis technique. Based on the results and analysis, the study shows that: (1) the implementation of Hindu Religious and Character Education in shaping the Pancasila Student Profile is carried out through comprehensive planning and strategies aimed at achieving character development goals; (2) the main learning models applied include discovery learning, cooperative learning, and project-based learning; and (3) the role of Hindu Religious and Character Education teachers in shaping the Pancasila Student Profile has a positive impact on enhancing students' morality and ethics, sharpening their critical and analytical thinking skills, and forming student personalities that are aligned with the noble values ​​of Pancasila.